2015
DOI: 10.1097/psy.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Adversity and Adult Biological Risk Profiles

Abstract: Objectives To determine whether there is a relationship between early life adversity (ELA) and biological parameters known to predict health risks and to examine the extent to which circumstances in midlife mediate this relationship. Methods We analyzed data on 1,180 respondents from the biomarker subsample of the second wave of the National Survey of Midlife Development in the United States (MIDUS) study. ELA assessments were based on childhood socioeconomic disadvantage (i.e. on welfare, perceived low inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
90
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 52 publications
9
90
0
1
Order By: Relevance
“…Fourth, consistent with prior work (Carroll et al 2013; Friedman et al 2015), we found the effects of childhood abuse remain significant even after controlling for several social characteristics, e.g., gender, race, childhood disadvantage. Both the severity and types of childhood abuse determined the magnitude of the poor biological profile.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fourth, consistent with prior work (Carroll et al 2013; Friedman et al 2015), we found the effects of childhood abuse remain significant even after controlling for several social characteristics, e.g., gender, race, childhood disadvantage. Both the severity and types of childhood abuse determined the magnitude of the poor biological profile.…”
Section: Discussionsupporting
confidence: 88%
“…However, previous studies have been limited to a single biomarker or physiological pathway. Two recent studies have investigated cumulative dysregulation across multiple systems (Carroll et al 2013; Friedman et al 2015), but these inquiries focused on only emotional and physical abuse. Finally, prior studies have not fully taken into account that dysregulation in stress hormones may present in different ways.…”
mentioning
confidence: 99%
“…These behaviors are associated with cardiovascular health problems, many of which are disproportionality represented among individuals living in lower SES neighborhoods. Furthermore, these behaviors are associated with higher allostatic load (Friedman, Karlamanga, Gruenewald, Koretz, & Seeman, 2015) and partially account for associations between lower individual SES and greater allostatic load (Gruenwald et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…En los estudios clínicos en los que se evalúan las consecuencias del maltrato infantil, el abandono materno y el estrés psicosocial, se sugiere que estos factores podrían favorecer el desarrollo de diversas enfermedades mentales, especialmente durante la adolescencia y la edad adulta (2)(3)(4). Se ha reportado que los niños abusados o rechazados por sus padres son más propensos a la depresión y a los trastornos de ansiedad, mientras que una relación estrecha y buena se asocia con un mejor manejo del estrés (5).…”
unclassified